Would the Urban Environmental Legislation Realize the Porter Hypothesis? Empirical Evidence Based on Panel Data of Chinese Prefecture Cities - Zhang, Fan; Yang, Yiwu; Ahmad, Mahmood; Shao, Junjie (Frontiers in Environmental Science, 2022)
The Porter hypothesis suggests that well-designed environmental regulation can trigger regional technological innovation that helps gain competitiveness. Little attention has been paid to whether China’s urban environmental legislation supports Porter hypothesis (PH). An empirical test was conducted based on panel data of 218 prefecture-level cities during 2003–2017 to examine the effects of urban environmental legislation on innovation and green total factor productivity (green TFP). The findings reveal that the urban environmental legislation increased the number of local green patents, which means that the weak Porter hypothesis was established. However, the urban environmental legislation did not lead to an increase in green TFP so that the strong version of PH did not hold. Further analysis showed that the urban environmental legislation led to the decline of green TFP and the increase of green patents in the west of China, but in the east and central cities, the changes were not visible. Besides, the legislation did not promote green TFP improvement through green innovation in the short term, which means it did not realize process compensation.